Landscape processes and management practices affecting phosphorous loss - Kortokrax, Abigail Rose (Kansas State University, 2023)
Phosphorous (P) loss from non-point agricultural sources is an important factor that affects the deterioration of surface water quality. Excessive P inputs can exacerbate eutrophication and toxic algal blooms, thus leading to greater water treatment costs and reduced recreational value of water bodies. To reduce non-point source P loss, we need to go back to the source and help farmers and ranchers make better land management decisions. One tool that can help is the P index. The P Index rating can provide information on major P loss pathways and help producers adjust land management decisions to minimize P loss from a specific field. Currently, the Kansas P index does not meet USDA-NRCS standards as listed in Title 190, which was updated in 2017. Among other items, updating the P index will require estimates of long-term annual runoff for soils and cropping systems across Kansas. Additional research is needed to identify a method of estimating runoff volume and to update the P index to current standards. Soil erosion presents one of the greatest concerns to most P mitigation programs worldwide because the majority of P loss occurs with eroded sediments. Ephemeral gully erosion is a type of erosion that can remove large quantities of sediment and is particularly difficult to control in no-till agriculture. Ephemeral gullies can develop in areas of concentrated flow within cultivated crop fields. Additional research is needed to identify best management practices that can reduce ephemeral gully erosion in no-till systems. The objectives of this research are to i) develop and evaluate a new approach to estimate long-term average annual runoff from agricultural fields, ii) develop a revised P index, and iii) investigate the effect of cover crops on ephemeral gully erosion. Two methods were evaluated to estimate long-term average annual runoff: use of the standard curve number (CN) approach with a daily time-step on long-term historical datasets (method 1) or a modified CN approach that uses long-term average annual rainfall and assumes an exponential distribution of rainfall (method 2). Both methods were calibrated and evaluated with edge-of-field monitoring data. The calibrated method 2 results revealed an R² = 0.88, NSE = 0.56 and when validating this method R² = 0.66, NSE = 0.54 indicating that this model had good model performance and that no further calibration was needed. The proposed P index is structured as a component P-index. Inputs were updated to include estimated average annual runoff calculated with the previously described modified CN approach. The coefficients for the P index components were developed through multiple linear regression with SAS proc mixed using a database of P loss estimates for 1360 cropping scenarios. Validation of the revised P index was conducted by relating the P index values to measured P loss data using both annual and summarized data from edge-of-field runoff experiments located in Riley, Crawford, Franklin, and Geary County. Coefficients to the revised P index were all significant at p<0.0001. Results showed that the proposed P index improved the relationship between the P index and P loss from R²= 0.41 to R²= 0.82 and validation of revised P index to the current index improved relationship between the P index and P loss from R²= 0.09 to R²= 0.71 using annual data and from R²= 0.73 to R²= 0.85 using average annual P loss data. The revised P index had improved model performance and would be a sufficient model to use for the Kansas P index. The final portion of this research was conducted in the summers of 2021 and 2022 at the Kansas Agricultural Watershed (KAW) field laboratory located near Manhattan, KS, USA. Ephemeral gully length, depth and width were measured and used to determine the volume of sediment lost through ephemeral gully erosion. Elevation data from an unmanned aerial vehicle (UAV) was collected in fall of 2016, 2020, and 2022 to determine ephemeral gully formations using ArcGIS Pro to compare elevation data. Results did not identify a significant effect of cover crops on ephemeral gully erosion. This could be due to insufficient ephemeral gully erosion in the watersheds at the KAW field lab. Furthermore, Elevation data collected by aerial imagery did not prove useful in quantifying the soil loss from ephemeral gullies. Results from this research will help producers and land managers more accurately evaluate effects of agricultural management systems on the risk of P loss to surface water using a revised P-index. The revised P index will also help producers identify the mechanisms responsible for P loss from their fields and thereby select conservation practice systems that can most effectively reduce those P losses.
Keywords: Phosphorus